FORMATION OF CRITICAL THINKING SKILLS IN METHODS OF METHODICAL PREPARATION STUDENTS OF PHILOLOGISTS - O.A. Pavlyk (Academy of Cognitive and Natural Sciences, 2022)
The article deals with lingual didactic problems of the development of critical thinking skills of students at lessons on methodic Ukrainian language learning. The author proposes educational methods, which of develop the critical thinking of students-philology.